Pengembangan Pop-Up Book berbasis Augmented Reality Materi Bangun Ruang Meningkatkan Self Efficacy Siswa Kelas V SDN Sumberdiren 01 Kabupaten Blitar - Wijono, Alifa Putri Sasmita Hadi; Alfi, Cindya; Fatih, Mohamad (Jurnal Simki Pedagogia, 2024)
The goal of this project is to improve the self-efficacy of 5th grade students through the development of augmented reality-based pop-up book learning materials and building spaces. Research and development (R&D) methodology is used in this project. The data was collected using surveys and interviews with instruments assessed by language, media, and material experts. The assessment from language experts received a score of 82.5%, meaning "very valid", the assessment from media experts received a score of 100%, meaning "very valid", and the product validity test from material experts received a score of 100%, meaning "very valid". With a score of 97.5% on the media attractiveness scale, it is classified in the "very interesting" category. Meanwhile, the increase in students' Self Efficacy was rated "high" with a score of 0.81. So it is concluded that the Augmented Reality-based Pop Up Book media is able to increase student self-efficacy.